Comparative Pharmacokinetics of Geniposidic Acid, Genipin-1-β-Gentiobioside, Geniposide, Genipin, and Crocetin in Rats after Oral Administration of Crude Gardeniae Fructus and Its Three Processed Products Using LC-MS/MS. (7th May 2020) - Yang, Xuejing; Li, Jin; Yang, Xi; He, Jun; Chang, Yan-Xu
Abstract : The extract of Gardeniae Fructus (GF) with different processing methods processed the different medicinal properties and efficacy. Crude GF (CGF) could be processed into stir-frying GF (SGF), gancao mix-frying GF (GCGF), and ginger mix-frying GF (GIGF) in practice. An LC-MS/MS method was established for simultaneous quantification of geniposidic acid, geniposide, genipin-1- β -gentiobioside, genipin, and crocetin in the rat plasma. The LLOQs for determination of all five components were 10 ng/mL. The accuracies of intraday and interday were in the range of 91%–105%. The recoveries of 5 analytes ranged from 81.0% to 114% with RSD less than 14%. The results showed that the AUCs (area under the plasma concentration-time curve) and C max (maximum plasma concentration) of geniposidic acid, genipin-1- β -gentiobioside, and geniposide after oral administration of the CGF extract were apparently higher than those after oral administration of other processed extracts. C max of geniposide in plasma after administration of GIGF significantly decreased (p < 0.01 ). Genipin was not detected in rat plasma after administration of the GIGF extract, but it can be detected in plasma after administration of CGF, SGF, and GCGF extract. Furthermore, crocin I and crocin II were not detected in plasma samples. Crocetin had higher concentration in rat plasma versus lower contents in extract. It was demonstrated that the different processing methods might influence the pharmacokinetics of geniposidic acid, genipin-1- β -gentiobioside, geniposide, genipin, and crocetin.